Probiotics, prebiotics and symbiotics attenuate chronic effects of passive smoking on physiological and biochemical parameters in rats: A randomized and controlled study (Research, Society and Development, 2021)
Passive and chronic exposure to tobacco smoke is a major cause of preventable diseases in humans and animals. The aim of this study was to evaluate the physiological and biochemical effects of functional foods: probiotics, prebiotics, and symbiotics in young rats exposed chronically to cigarette smoke. Ninety-six young male rats were randomly assigned to eight groups (n = 12): control (C); probiotic (Pro); prebiotic (Pre); symbiotic (Sym); smoking control (CS); smoking probiotic (ProbS); smoking prebiotic (PrebS); and smoking symbiotic (SymbS). After the experimental period of 189 days, the animals were anesthetized, blood samples were collected, and the animals were euthanized by exsanguination. The data were submitted to the Shapiro Wilk test, followed by the one-way ANOVA test, with contrasts by the Tukey method (P